Eastward enlargement of the EU: Will agricultural policy be an obstacle? - Stefan Tangermann (Intereconomics, 1995)
The political preparations for enlarging the European Union to include the Central European countries are in full swing, but economic policy preparations have not yet begun. There is a need for adjustment primarily in the Central European countries, but also in sensitive areas in the EU itself, particularly the Common Agricultural Policy. Will agricultural policy be an obstacle to eastward enlargement?
Keywords: 330; EU